2009
DOI: 10.1111/j.1600-0706.2009.17601.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐random recruitment of invader species in experimental grasslands

Abstract: To assess potential effects of seed limitation, characteristics of invader species and characteristics of established plant communities on recruitment success, we conducted a split‐plot experiment factorially combining three weeding treatments corresponding to increasing successional age (regular weeding Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 70 publications
1
18
0
Order By: Relevance
“…A second mechanism is recruitment limitations when plant life cycles cannot be completed and the regeneration of new plant individuals is reduced causing a decrease in plant population sizes over time (Symstad and Tilman 2001). In fact, the regeneration of many species in the Jena Experiment has been demonstrated to be seed-limited, with strongest effects in low-diversity communities (Roscher et al 2009b), and patterns observed for plant cover support this interpretation. A third mechanism is the reduced capacity for temporal turnover between species in low-diversity communities; this turnover is important for maintaining functions such as plant productivity, as different species respond to environmental fluctuations differently (Allan et al 2011).…”
Section: Discussionmentioning
confidence: 97%
“…A second mechanism is recruitment limitations when plant life cycles cannot be completed and the regeneration of new plant individuals is reduced causing a decrease in plant population sizes over time (Symstad and Tilman 2001). In fact, the regeneration of many species in the Jena Experiment has been demonstrated to be seed-limited, with strongest effects in low-diversity communities (Roscher et al 2009b), and patterns observed for plant cover support this interpretation. A third mechanism is the reduced capacity for temporal turnover between species in low-diversity communities; this turnover is important for maintaining functions such as plant productivity, as different species respond to environmental fluctuations differently (Allan et al 2011).…”
Section: Discussionmentioning
confidence: 97%
“…Higher levels of realized species richness after seed addition are commonly found because plant communities are often under-saturated with species due to a limited species pool or dispersal constraints [44], [45]. Although none of the species added as seed failed to establish completely after seed addition [21] and single communities accumulated indeed up to 60 species one or two years after seed addition, average species richness in the seed addition treatments declined again and did not exceed 35 species in the last year of the study (Fig. 2A).…”
Section: Discussionmentioning
confidence: 99%
“…We also investigated phylogenetic pattern in a reassembly experiment carried out in all 78 plots; monocultures and two-species plots were included because species numbers rapidly increased during reassembly (Roscher et al 2009a). In this experiment, seeds of all 60 species were sown, in April 2005, at equal proportions and at a total density of 1000 viable seeds/ m 2 , into the existing vegetation in subplots of 2.00 3 2.25 m. Species not belonging to the species pool continued to be weeded out from July 2005.…”
Section: The Jena Experimentsmentioning
confidence: 99%